Wave In in auditory brainstem response suggests a high possibility of a high jugular bulb - Liu, Jia; Xie, Wanqin; Ding, Yan; Hu, Ya; Lai, Ruosha; Hu, Peng; Zhu, Ganghua (Frontiers in Pediatrics, 2023)
Background Wave In, which refers to the negativity between waves I and II in auditory brainstem response (ABR), is an electrophysiological phenomenon observed in previous studies. The term “high jugular bulb” (HJB) describes a jugular bulb that is located in a high position in the posterior aspect of the internal acoustic canal. The present study aimed to explore the correlation between wave In and the possibility of a HJB. Methods This retrospective study included a cohort of pediatric patients diagnosed with profound hearing loss who were enrolled in a government-sponsored cochlear implantation program at an academic medical center between January 2019 and December 2022. The analysis involved examining the results obtained from the ABR test and high-resolution computed tomography (HRCT) of the temporal bone in the patients. The position of the jugular bulb was classified according to the Manjila and Semaan classification. Results A total of 221 pediatric patients were included in the study. Twenty-four patients, with a median age of 3 years and a range of 1–7 years, showed significant bilateral (n = 21) or unilateral (n = 3) wave In (mean latency: right ear, 2.16 ms ± 0.22 ms; left ear, 2.20 ms ± 0.22 ms). The remaining 197 patients showed an absence of ABR. The HRCT images revealed that 18 of the 24 patients (75%) had HJB, but only 41 of the 197 patients who lacked ABR (20.8%) showed signs of HJB. The ratio difference was considered statistically significant based on the chi-squared test (χ2 = 32.10, p < 0.01). More than 50% of the HJBs were categorized as type 4 jugular bulbs, which are located above the inferior margin of the internal auditory canal. Conclusion ABR wave In in pediatric patients with profound hearing loss suggests a high possibility of HJB. The physiological mechanism underlying this correlation needs further investigation.